Philosophical Analysis of Special Village Development Areas Based on Local Potential to Achieve Village Independence (Empirical Study in Bojong Village, Bungbulang) - Aip Zaenal Mutaqin; Lukman Nulmunir; Yusuf Musyaffa; Mulyaningsih (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
This study aims to analyze the implementation of economic development in Bojong Village, Bungbulang District, Garut Regency, by referring to the theory of Special Area Village Development, while also examining the philosophical basis of development and empowerment of rural economy in an effort to realize Independent Village. Bojong Village is an agrarian area that has abundant natural resources, including 350-350 Ha of rice fields, 1,200-1,200 Ha of forest area, seven waterfalls, and potential A (gold) mining of 8080 Ha. However, this village faces major problems in the form of high unemployment and social welfare issues, which are seen from the dominance of livelihoods as farm laborers (885-885 people) and the existence of 180-180 units of uninhabitable houses (RTLH). The study uses a descriptive qualitative approach by utilizing the 2025 Village Profile data as a source of analysis. The results of the philosophical-critical analysis indicate an imbalance in the distribution between the wealth of extractive resources (gold) and the low level of welfare of poor community groups (PMKS). The ongoing development is considered not to fully reflect the principles of Distributive Justice (Rawls, 1999) or the concept of Authentic Empowerment (Friedmann, 1992). Therefore, this study recommends the integration of Special Area programs that emphasize economic diversification towards more sustainable ecotourism and cultural sectors, and are reinforced by a transformative public administration philosophy to ensure substantive community autonomy in managing village assets. Keywords: Local Potential Base, Special Area Village Development, Village Independence